Integrability of the n-center problem at high energies - Knauf, Andreas; Taimanov, Iskander A. (Doklady Mathematics, 2004)
It is shown that for generic configuration of the centres at high energy levels the n-centre problem is completely integrable by using C^∞ integrals of the motion however it is not integrable in terms of real analytic functions